The Relationship between Intelligence Quotient with Variables among Kindergarten Children in Khartoum State - Jafar, Nada Izzeldeen (Journal of Educational and Psychological Sciences, 2025)
This study tries to investigate the Relationship between Intelligence Quotient with Variables among Kindergarten Children in Khartoum State Descriptive method adopted to achieve the objectives of the current study. Simple stratified random method is applied to select sample of (300) subjects. The tool of da collection comprises the following: Raven s Coloured Progressive Matrices Tests, the practical part of Wechsler Intelligence scale for Children (WPPSI), and Bibliographical sheetta, sheet. Statistical Packages for Social Sciences (SPSS) applied in analyzing the data using (T) test, and person correlation coefficient. The most important findings of the study are as follows: There is no statistical significant difference in intelligence quotient among kindergarten according to gender (Male, Female) Results also indicate that there is a significant correlation coefficient between intelligence quotient with level of performance in accuracy and speed. There is no significant correlation coefficient between intelligence quotient with birth- order and parent’s education. The study also postulated some recommendations according to its result, i.e. to investigate the most effective method of children, and means of enhancing children's abilities.
Keywords: Intelligence Quotient; Variables; Kindergarten Children